2005
DOI: 10.1152/ajpcell.00543.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 MAPKα by extracellular pressure mediates the stimulation of macrophage phagocytosis by pressure

Abstract: We have previously demonstrated that constant 20 mmHg extracellular pressure increases serumopsonized latex bead phagocytosis by phorbol 12-myristate 13-acetate (PMA)-differentiated THP-1 macrophages in part by inhibiting focal adhesion kinase (FAK) and extracellular signal-regulated kinase (ERK). Because p38 MAPK is activated by physical forces in other cells, we hypothesized that modulation of p38 MAPK might also contribute to the stimulation of macrophage phagocytosis by pressure. We studied phagocytosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 89 publications
(113 reference statements)
5
38
0
Order By: Relevance
“…Exposure to pressure increased phagocytosis in monocytes from healthy volunteers (22.9 Ϯ 3.3 vs. 31.8 Ϯ 4.7%, n ϭ 8, P Ͻ 0.005; Fig. 1A), consistent with our previous observations (51,52). However, pressure failed to increase phagocytosis in monocytes isolated from surgical patients receiving anesthesia (Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Exposure to pressure increased phagocytosis in monocytes from healthy volunteers (22.9 Ϯ 3.3 vs. 31.8 Ϯ 4.7%, n ϭ 8, P Ͻ 0.005; Fig. 1A), consistent with our previous observations (51,52). However, pressure failed to increase phagocytosis in monocytes isolated from surgical patients receiving anesthesia (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We previously reported that increased extracellular pressure (20 mmHg above ambient pressure) stimulates serum-opsonized latex bead uptake by primary isolated monocytes from healthy volunteers as well as PMA-differentiated human monocytic THP-1 cells (THP-1 macrophages) (51)(52)(53). Several reports suggest that anesthetic agents and surgical stress may affect phagocytic cell function (5,23,28) and that tissue pressure may be increased within surgical wounds or at surgical sites postoperatively (56).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations